Dislokasi Kiri dalam Bahasa Indonesia - Ikmi Nur Oktavianti (Balai Bahasa Provinsi Papua, 2019)
Information can be packaged based on the need of the speaker and best described in information structure. The selection of a certain package in using language is not aimless. There is special intention owned by the speaker. Left-dislocation is recognized as one of the way to package the information. Due to its uncommon use, left-dislocation construction is a non-canonical way to arrange the information flow. This paper will attempt to portray left-dislocation in bahasa Indonesia based on syntactic view and a slight analysis based on discourse view. The portrayal will deal with kinds of left-dislocation, the relationship of antecedant – pronoun and the discourse function of left-dislocation.